(untitled) (Journal of Shaheed Suhrawardy Medical College, 2019)
Background: The rising incidence of caesarean section all over the world has been of great concern both to the patients and obstetrician.1 Repeat caesarean section is one of the major reasons which have contributed greatly to high caesarean section (CS) rate.1,2 Although maternal death as a result of CS is now rare, reports of the short-and long-term consequences of the rising CS rate on the childbearing population are conflicting.3 Available data show that repeat caesarean section is associated with many maternal complications, specially intra-abdominal adhesions, central placenta praevia, uterine rupture, caesarean scar pregnancy, caesarean hysterectomy etc.4 Objective: To evaluate outcome and complications of multiple repeat caesarean section. Methodology: This was a cross sectional prospective study conducted in Shaheed Suhrawardy Medical College Hospital (ShSMCH) from 1st June’2016 to 30th November’2016 for a period of six months. The study population were 102 patients, selected randomly who were admitted in ShSMCH for repeat caesarean section. Results: Out of 102 patients admitted with history of previous caesarean section, maternal morbidity was 26 (25.49%), which includes intra-abdominal adhesions 19 (18.62%), excessive blood loss 6(5.88%), placenta praevia 4 (3.94%), placenta accreta 1 (.98%), postpartum haemorrhage 11 (10.78%), wound infection 12 (11.76%) etc. Conclusion: As the rate of repeat caesarean section continue to rise, surgeons should be more judgemental in doing caesarean section. J Shaheed Suhrawardy Med Coll, December 2018, Vol.10(2); 74-79